The Tourism Resources Management Process Administration in Territorial Communities under Crisis Conditions - Chernysh, Iryna; Glebova, Alla; Makhovka, Viktoriia; Bilousova, Anastasia (International Journal of Engineering and Technology, 2018)
The article explores the process of tourist resources management at the level of local communities. It is determined that at the present stage, in the conditions of decentralization of the rights and powers of the authorities, these are the territorial communities that will manage resources. Since tourism is an industry that has a high competition level, it is necessary to constantly adapt the management system to the realities. The authors proposed the creation of a virtual tourist cluster, which will ensure effective administration of tourist resources at the community level. The main participants of the virtual tourist cluster and the organizational economic interaction mechanism are determined.Â Â